Graphite material densification method and high-density graphite

Through chemical vapor-phase penetration density enhancement technology and multiple graphitization treatments, the graphite material is gradually filled, solving the problems of porous structure inside the raw material and the filling and blocking of graphitized air pores, and achieving high density and strength improvement of graphite material.

CN119684002APending Publication Date: 2025-03-25SINOSTEEL NANJING NEW MATERIALS RES INST CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411705762.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The prior art is difficult to further increase the density of artificial graphite materials, mainly because the porous structure inside the raw material is difficult to effectively fill, and the pores generated during the graphitization process cannot be effectively filled.

Method used

The graphite raw materials are processed by chemical vapor-phase penetration and density enhancement technology, and carbon is deposited to the interior and surface of the pores of the raw material, and the pores are filled through multiple graphitization and impregnation treatments, and finally the high density of the graphite material is achieved through chemical vapor-phase penetration and density enhancement.

Benefits of technology

The volume density of graphite material has been significantly improved to reach ≥1.96g/cm3, solving the problem of poor density, and enhancing the strength and density of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a densification method of a graphite material and high-density graphite, and belongs to the technical field of graphite material preparation. Comprising the following steps: crushing raw material calcined pitch coke or petroleum coke into coarse particles, and then carrying out chemical vapor infiltration densification to obtain a densified coarse particle raw material; crushing the partially densified coarse particle raw materials into different particle fractions, and respectively kneading and grinding the coarse particle raw materials with asphalt to obtain paste fine powder with different particle fractions; uniformly mixing the residual densified coarse particle raw material with the paste fine powder of different size fractions, molding, roasting, dipping and graphitizing, and circulating twice to obtain a secondarily graphitized graphite material; and carrying out chemical vapor infiltration densification on the secondarily graphitized graphite material, and then carrying out third graphitization to realize densification of the graphite material. Carbon is subjected to gas phase permeation and deposited to the interiors and surfaces of pores of the raw materials, the strength and compactness of the raw materials are improved, and the problem of poor compactness of graphite products is solved from the source.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of graphite material preparation, and in particular relates to a densification method for graphite material and high-density graphite. Background Art

[0002] Graphite materials are widely used in nuclear power, aerospace, metallurgy, chemical industry, machinery, medical, electronics and other fields due to their high temperature resistance, high conductivity, high strength and corrosion resistance. With the development of the industry, higher requirements are placed on artificial graphite materials.

[0003] Increasing the density of artificial graphite materials to improve material performance is a direction for the development of the industry, but also a difficulty. The existing densification technology mainly optimizes the formulation, molding, impregnation and roasting processes before graphitization to reduce the internal pores of the blank, thereby increasing the density of the material. However, no matter what kind of optimization is used, it is difficult to continue to increase the material density after a certain increase. The root cause lies in the density defects of the raw materials themselves. The raw materials of graphite materials are mainly petroleum coke or asphalt coke, which have a loose and porous structure inside. After grinding, the original structure is still maintained. It is difficult to effectively fill this part of the pores with subsequent densification. The preparation of graphite with this type of raw material will inevitably lead to poor density of the final product. In addition, after graphitization, the impurity components in the blank gradually escape, and new pores are generated inside. The existing process ignores the filling and plugging of the pores generated by graphitization, resulting in poor performance of the graphite material.

[0004] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention

[0005] In order to solve the technical problem of difficulty in further densifying artificial graphite materials in the prior art, a densification method for graphite materials and high-density graphite are provided.

[0006] A first aspect of the present invention provides a method for densifying a graphite material, comprising the following steps:

[0007] (1) crushing the raw material calcined asphalt coke or petroleum coke into coarse particles, and then performing chemical vapor infiltration densification to obtain a densified coarse particle raw material;

[0008] (2) Taking part of the densified coarse granular raw materials and crushing them into different particle sizes, and mixing and grinding them with asphalt respectively, to obtain paste fine powders of different particle sizes; generally, asphalt with a softening point of 90 to 120°C is selected, and the asphalt dosage is 28 to 32%;

[0009] (3) the remaining densified coarse particle raw material is mixed with the paste fine powder of different particle sizes to form a uniform shape, and then roasted, impregnated and graphitized, and after two cycles, a secondary graphitized graphite material is obtained;

[0010] (4) After the secondary graphitized graphite material is subjected to chemical vapor infiltration densification, a third graphitization is performed to achieve densification of the graphite material.

[0011] In some embodiments, the gases used in the chemical vapor infiltration are CH4 and CO2.

[0012] In some embodiments, the volume ratio of CH4 to CO2 is 5 to 9:1.

[0013] In some embodiments, the chemical vapor infiltration pressure is 0.01-0.05 MPa, the temperature is 900-1100° C., and the working time is 30-60 h;

[0014] And / or, vacuum is applied before chemical vapor infiltration, and the vacuum pressure is less than 100 Pa.

[0015] In some embodiments, the average particle size of the coarse particles is 1 to 5 mm.

[0016] In some embodiments, the coarse particles in step (2) are crushed into fine powders with an average particle size of 0.1 to 0.5 mm and 5 to 20 μm;

[0017] And / or, the average particle size of the paste fine powder in step (2) is 0.1-1 mm and 20-40 μm.

[0018] The paste fine powder is controlled to have a larger average particle size than the raw material fine powder after densification to avoid the destruction of the raw material fine powder particles.

[0019] In some embodiments, in step (3), the weight ratios of the coarse particle raw material, 0.1-1 mm paste fine powder and 20-40 μm paste fine powder are 40-70:10-20:20-40 respectively.

[0020] In some embodiments, the roasting and impregnation in step (3) are performed in a two-impregnation and three-roasting manner. The two-impregnation and three-roasting are roasting, impregnation, roasting, re-impregnation, and re-roasting. Since roasting is performed first after forming, multiple impregnation and roasting are performed according to the situation. Since roasting must be performed after each impregnation, the number of roasting times is one more than the number of impregnation times.

[0021] In some embodiments, the calcination temperature in step (3) is 750-1000° C., and the holding time is ≥6 h;

[0022] And / or, in step (3), the immersion temperature is 180-250° C., the immersion time is ≥0.5 h, and the immersion pressure is 0.8 MPa-5 MPa;

[0023] And / or, in the step (3), the graphitization time is ≥148 h and the maximum temperature is not less than 2900° C.

[0024] The second aspect of the present invention provides a high-density graphite prepared by the above-mentioned densification method, wherein the volume density of the high-density graphite is ≥1.96g / cm 3 .

[0025] By adopting the technical solution of the present invention, the technical effects achieved are as follows:

[0026] (1) The present invention performs chemical vapor infiltration densification treatment on graphite raw materials, and through vapor infiltration and deposition of carbon into the pores and surface of the raw materials, the strength and density of the raw materials are improved, thereby solving the problem of poor density of graphite products from the source.

[0027] (2) A partial kneading process is used to crush part of the densified coarse particles into fine particles, and only the fine particles are kneaded with asphalt, thereby reducing the amount of asphalt used and the defects caused by excessive volatiles in the asphalt. At the same time, the dense internal structure of the coarse particles is protected and enhanced, ensuring that the graphite product has a higher density.

[0028] (3) The present invention divides the paste of different particle sizes of the densified coarse particles into subdivided materials and mixes them in a certain proportion. This can avoid the coarse particles from being destroyed and protect the strength of the coarse particles. It can also effectively increase the packing density and reduce the amount of asphalt, thereby improving the product density.

[0029] (4) The graphitized graphite product is subjected to impregnation, calcination, secondary graphitization and chemical vapor infiltration, and tertiary graphitization treatment to progressively fill the pores generated by the previous graphitization, thereby greatly improving the density of the final graphite product. DETAILED DESCRIPTION

[0030] The following combined schemes illustrate the technical scheme of the present invention through specific embodiments. It should be understood that one or more steps mentioned in the present invention do not exclude the existence of other methods and steps before and after the combined steps, or other methods and steps can be inserted between these explicitly mentioned steps. It should also be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Unless otherwise specified, the numbering of each method step is only for the purpose of identifying each method step, rather than limiting the order of arrangement of each method or limiting the scope of implementation of the present invention. Changes or adjustments in their relative relationships can also be regarded as the scope of implementation of the present invention without substantial changes in the technical content.

[0031] The sources of the raw materials and instruments used in the examples are not particularly limited and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0032] Example 1

[0033] (1) The raw material calcined asphalt coke was crushed into coarse particles with an average particle size of 3 mm, and then placed in a chemical vapor infiltration furnace for infiltration densification treatment. Before densification, the vacuum was evacuated to 30 Pa, and then the temperature was raised to 1100 ° C. A mixed gas of CH4 and CO2 with a volume ratio of 9:1 was introduced at a rate of 200 ml / min, and the pressure in the furnace was maintained at 0.02 MPa. The infiltration densification time was 50 h;

[0034] (2) taking part of the densified coarse particle raw material, grinding it into two kinds of fine powders with average particle sizes of 0.3 mm and 10 μm, respectively mixing them with asphalt, the asphalt amounts after mixing are 28.5% and 30.5% respectively, and grinding them into paste fine powders with average particle sizes of 0.5 mm and 20 μm, controlling the weight ratio of 3 mm coarse particle raw material, 0.5 mm paste fine powder and 20 μm paste fine powder to be 70%:10%:20%, and mixing them evenly;

[0035] (3) isostatically pressing the mixture, followed by calcination, impregnation, secondary calcination and graphitization;

[0036] (4) The graphitized product is impregnated, calcined, and subjected to secondary graphitization treatment, followed by chemical vapor infiltration densification and tertiary graphitization. The chemical vapor infiltration densification conditions are the same as those in step (1), thereby obtaining a densified graphite material. The final graphite product has a volume density of 1.98 g / cm 3 .

[0037] Example 2

[0038] (1) The raw material calcined asphalt coke was crushed into coarse particles with an average particle size of 5 mm, and then placed in a chemical vapor infiltration furnace for infiltration densification treatment. Before densification, the vacuum was evacuated to 50 Pa, and then the temperature was raised to 1200 ° C, and a mixed gas of CH4 and CO2 with a volume ratio of 6:1 was introduced at a rate of 300 ml / min, the pressure in the furnace was maintained at 0.05 MPa, and the infiltration densification time was 40 h;

[0039] (2) taking part of the densified coarse particle raw material, grinding it into two kinds of fine powders with average particle sizes of 0.2 mm and 5 μm, respectively, kneading them with asphalt, the amount of asphalt after kneading is 28.8% and 31.3% respectively, and grinding them into paste fine powders with average particle sizes of 0.4 mm and 10 μm, controlling the weight ratio of 5 mm coarse particle raw material, 0.4 mm paste fine powder and 10 μm paste fine powder to be 50%:15%:35%, and mixing them evenly;

[0040] (3) isostatically pressing the mixture, followed by calcination, impregnation, secondary calcination and graphitization;

[0041] (4) The graphitized product is impregnated, calcined, and subjected to secondary graphitization treatment, followed by chemical vapor infiltration densification and tertiary graphitization. The chemical vapor infiltration densification conditions are the same as those in step (1), thereby obtaining a densified graphite material. The final graphite product has a volume density of 1.96 g / cm 3 .

[0042] Example 3

[0043] (1) The raw material calcined asphalt coke was crushed into coarse particles with an average particle size of 1 mm, and then placed in a chemical vapor infiltration furnace for infiltration densification treatment. Before densification, the vacuum was evacuated to 20 Pa, and then the temperature was raised to 1150 ° C, and a mixed gas of CH4 and CO2 with a volume ratio of 7:1 was introduced at a rate of 100 ml / min, and the pressure in the furnace was maintained at 0.04 MPa. The infiltration densification time was 50 h;

[0044] (2) taking part of the densified coarse particle raw material, grinding it into two kinds of fine powders with average particle sizes of 0.1 mm and 5 μm, respectively, kneading them with asphalt, the asphalt contents after kneading are 28.8% and 31.3% respectively, and grinding them into paste fine powders with average particle sizes of 0.2 mm and 10 μm, controlling the weight ratio of 1 mm coarse particle raw material, 0.2 mm paste fine powder and 10 μm paste fine powder to be 60%:15%:25%, and mixing them evenly;

[0045] (3) isostatically pressing the mixture, followed by calcination, impregnation, secondary calcination and graphitization;

[0046] (4) The graphitized product is impregnated, calcined, and subjected to secondary graphitization treatment, followed by chemical vapor infiltration densification and tertiary graphitization. The chemical vapor infiltration densification conditions are the same as those in step (1), thereby obtaining a densified graphite material. The final graphite product has a volume density of 1.97 g / cm 3 .

[0047] Comparative Example 1

[0048] The same method as in Example 1 was used, except that the raw materials were not subjected to chemical vapor densification treatment. The final graphite product had a body density of 1.91 g / cm 3 .

[0049] Comparative Example 2

[0050] The same method as in Example 1 is used, except that all the densified coarse particles are ground, kneaded, and ground again, that is, all the densified coarse particles are ground to three particle sizes of 3 mm, 0.3 mm, and 10 μm, and the three particle size densified raw materials are kneaded with asphalt to obtain three pastes, which are then ground in turn to obtain 2 mm, 0.5 mm, and 20 μm pastes, and the three particle size pastes are mixed and formed, and the rest is the same as in Example 1. The obtained graphite product has a volume density of 1.89 g / cm 3 This is because all the densified coarse particles mixed with asphalt will lead to the destruction of the coarse particles and the increase of asphalt dosage, thus reducing the density of the final product.

[0051] Comparative Example 3

[0052] The same graphite raw material as in Example 1 was used, except that no densification treatment after graphitization was performed, that is, step (4) in Example 1 was not performed. The final graphite product obtained had a body density of 1.94 g / cm 3 .

[0053] Comparative Example 4

[0054] The same method as in Example 1 was used, except that the densification was performed after crushing into 0.5 mm, and then part of the densified raw material was crushed into 0.2 mm and 5 μm. The three kinds of raw materials were equal in amount, and the final graphite product had a density of 1.91 g / cm 3

[0055] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. A method for densifying a graphite material, characterized in that: The steps include: (1) crushing the raw material calcined asphalt coke or petroleum coke into coarse particles, and then performing chemical vapor infiltration densification to obtain a densified coarse particle raw material; (2) taking part of the densified coarse granular raw materials and crushing them into different particle sizes, and mixing and grinding them with asphalt respectively to obtain paste fine powders of different particle sizes; (3) the remaining densified coarse particle raw material is mixed evenly with the paste fine powder of different particle sizes, and then formed, and roasted, impregnated and graphitized, and after two cycles, a secondary graphitized graphite material is obtained; (4) After the secondary graphitized graphite material is densified by chemical vapor infiltration, a third graphitization is performed to achieve densification of the graphite material.

2. The densification method according to claim 1, characterized in that: The gases used in the chemical vapor infiltration are CH4 and CO2.

3. The densification method according to claim 2, characterized in that: The volume ratio of CH4 to CO2 is 5 to 9:

1.

4. The densification method according to claim 1, characterized in that: The pressure of the chemical vapor infiltration is 0.01-0.05 MPa, the temperature is 900-1100°C, and the working time is 30-60 hours; And / or, vacuum is applied before chemical vapor infiltration, and the vacuum pressure is less than 100 Pa.

5. The densification method according to claim 1, characterized in that: The average particle size of the coarse particles is 1 to 5 mm.

6. The densification method according to claim 1, characterized in that: In the step (2), the coarse particles are crushed into fine powder with an average particle size of 0.1 to 0.5 mm and 5 to 20 μm; And / or, the average particle size of the paste fine powder in step (2) is 0.1-1 mm and 20-40 μm.

7. The densification method according to claim 6, characterized in that: In the step (3), the weight proportions of the coarse particle raw material, 0.1-1 mm paste fine powder and 20-40 μm paste fine powder are 40-70:10-20:20-40 respectively.

8. The densification method according to claim 1, characterized in that: In the step (3), the roasting and impregnation are carried out in a two-impregnation and three-roasting manner.

9. The method according to claim 1, wherein the calcination temperature in step (3) is 750-1000°C and the holding time is ≥ 6h; And / or, in step (3), the immersion temperature is 180-250° C., the immersion time is ≥0.5 h, and the immersion pressure is 0.8 MPa-5 MPa; And / or, in the step (3), the graphitization time is ≥148 h and the maximum temperature is not less than 2900° C.

10. A high-density graphite, characterized in that: Prepared by the densification method according to any one of claims 1 to 9, the volume density of the high-density graphite is ≥ 1.96 g / cm 3 .

Citation Information

Cited By

  • Graphite sagger and preparation method and application thereof

    CN120463499A